Model Kajian Pendekatan Manajemen Strategik Dalam Peningkatan Sektor UMKM Di Kota Bandung (Model Study of Strategic Management Approach In SMEs Sector Improvement In Bandung) - Senen Machmud; Iwan Sidharta (STMIK Mardira Indonesia, Bandung, 2015)
SMEs are an important part to be developed by local governments. In developing the SME needs to be a comprehensive study models so easy in policy formulation, program development and SME development activities, especially in Bandung in accordance with the vision and mission to build dignified Bandung. This study uses a conceptual approach to the strategic management approach to making models of the development of SMEs in Bandung. This study models can generate referrals and a description of the formulation of policies, programs, and activities that can develop SMEs in Bandung that can increase social welfare. Keywords: strategic management; SMEs; entrepreneurship